INSTITUTE OF SAFETY OF CRIMINAL PROCESS PARTICIPANTS: THE COMPARATIVE ANALYSIS OF THE FOREIGN COUNTRIES LEGISLATION - A. Ju. Epihin (Russian Journal of Economics and Law, 2008)
The problem of personal safety in the sphere of the criminal trial in the domestic legislation became actual only in the last two decades. At the same time, legal regulation of safe conditions of sharing in criminal proceeding in foreign countries is already solved. The analysis given by the author shows the possibility of use of normative foreign experience in the Russian legislative practice with the purpose of more effective prevention of crime.